A Study on the Role of Tourism in Destination’s Disaster and Resilience Management - NAIR, Bipithalal Balakrishnan; DILEEP, M.R (Journal of Environmental Management and Tourism, 2020)
Tourism is one of the most sensitive and vulnerable sectors to a disaster. On the one hand, the industry is susceptible to these unprecedented adversities and is a sufferer. On the other hand, tourism significantly contributes to and performs central roles in crisis management and a destination’s resilience. Comparatively, the latter topic remains under-researched and fewer studies were focused on the part of tourism as a benefactor. However, due to the intricacy and scope of a global crisis, as an accountable service business, it is significant to understand in what ways tourism benefits a (developing) destination throughout various phases of the crisis. Therefore, this study attempts to understand the crucial role of tourism in the case of the catastrophic flood that occurred in Kerala, India, by adopting the crisis management model proposed by Faulkner. The study findings underline the pivotal role of the tourism industry in rescue, restoration, information & communication, and resilience strategy. Furthermore, the study comes up with several unanticipated yet vital insights about the importance of corporate social responsibility for tourism industries, the inevitable role of tourism stakeholders in disaster management strategies, and the importance of adopting appropriate post-disaster marketing plans to support the rebuilding of the destination.